Oil Prices, External Income, and Growth : Lessons From Jordan - Raissi, Mehdi; Mohaddes, Kamiar (Washington, D.C. : International Monetary Fund, 2011)
This paper extends the long-run growth model of Esfahani and others (2009) to a labor exporting country that receives large inflows of external income?the sum of remittances, FDI and general government transfers?from major oil-exporting economies. The theoretical model predicts real oil prices to be one of the main long-run drivers of real output. Using quarterly data between 1979 and 2009 on core macroeconomic variables for Jordan and a number of key foreign variables, we identify two long-run relationships: an output equation as predicted by theory and an equation linking foreign and domestic inflation rates. It is shown that real output in the long run is shaped by: (i) oil prices through their impact on external income and in turn on capital accumulation, and (ii) technological transfers through foreign output. The empirical analysis of the paper confirms the hypothesis that a large share of Jordan's output volatility can be associated with fluctuations in net income received from abroad. External factors, however, cannot be relied upon to provide similar growth stimuli in the future, and therefore it will be important to diversify the sources of growth in order to achieve a high and sustained level of income.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet